Inventory of Epiphytic Ferns in Tanta Village, Tabalong District, South Kalimantan - Nisa, Hayatun; Mahrudin, Mahrudin; Utami, Nurul Hidayati (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
The diversity of ferns species is very high, one type of fern that is often found in the forests of Kalimantan is the epiphytic fern. Epiphytic ferns are ferns that attach to host trees which are often found in forests with high humidity. From an ecological perspective, epiphytic ferns in Tanta Village have an important role in the environment, especially river border areas, for example as a place for small animals to live and as producers in the food chain. In terms of its benefits for humans in Tanta Village, people use it as an ornamental plant, medicine, handicraft or food. This research aims to inventory epiphytic ferns in Tanta Village, Tabalong Regency, South Kalimantan. Data collection was obtained using total techniques. The results of the research found that there were 7 types of epiphytic ferns, namely: Davallia denticulata, Asplenium nidus L., Nephrolepis biserrata, Drynaria sparsisora, Pyrrosia lanceolata, Drymoglossum piloselloides, and Microsorum punctatum. From this research it can be concluded that the seven types of epiphytic ferns can be found in the riverbank area of Tanta Village because this area is suitable for supporting the life of epiphytic ferns.